2023
DOI: 10.15586/aei.v51i1.737
|View full text |Cite
|
Sign up to set email alerts
|

TRIM52 aggravated inflammation and pyroptosis in dextran sulfate sodium-induced inflammatory bowel disease through activation of the TLR4/NF-κBs pathway

Abstract: Introduction: Inflammatory bowel disease (IBD), which mainly leads to diarrhea, fatigue, stool blood, abdominal pain, and cramping, is threatening public health. Tripartite motif-containing 52 (TRIM52) has been reported to play an important role in inflammatory responses via activating the toll-like receptor 4 (TLR4)/nuclear factor-κB (NF-κB) pathway. However, the causes of IBD need to be elucidated, and the function of TRIM52 in IBD remains unclear. Here, we demonstrated that TRIM52 aggravated inflammation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…In line with these studies, the importance of zTLR4ba to SpaC‐induced pyroptosis was also validated by the knockdown of TLR4ba in zebrafish larvae. In line with our findings, the inhibition or activation of the TLR4 signal pathway can inhibit or activate intestinal pyroptosis in mammals [ 69 , 70 , 71 , 72 ]. Therefore, the causal functional relationship between TLR4 signaling and cell pyroptosis is conserved among zebrafish and mammals.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In line with these studies, the importance of zTLR4ba to SpaC‐induced pyroptosis was also validated by the knockdown of TLR4ba in zebrafish larvae. In line with our findings, the inhibition or activation of the TLR4 signal pathway can inhibit or activate intestinal pyroptosis in mammals [ 69 , 70 , 71 , 72 ]. Therefore, the causal functional relationship between TLR4 signaling and cell pyroptosis is conserved among zebrafish and mammals.…”
Section: Discussionsupporting
confidence: 90%
“…Seven membrane receptors were screened by using pull‐down assay conjugating LC−MS/MS technique, including TLR4ba. Among these receptors, existing reports suggest that only TLR4 is reported to control pyroptosis in mammals [ 69 , 70 , 71 , 72 ]. In line with these studies, the importance of zTLR4ba to SpaC‐induced pyroptosis was also validated by the knockdown of TLR4ba in zebrafish larvae.…”
Section: Discussionmentioning
confidence: 99%
“…TRIM52 has been under positive selection pressure in humans and old-world primates. In contrast to other TRIM proteins with similar evolutionary patterns-like TRIM5α-no evidence has been found for direct anti-retroviral activity of TRIM52 6 , although some studies have reported a role in defenses against other viruses and inflammatory signaling 10,[54][55][56] . In agreement with cell-intrinsic selection pressure, rather than pressure exclusively from exogenous pathogens, we found that TRIM52 ablation decreased cellular fitness in a p53-dependent manner, in the absence of external stimuli 8,9 .…”
Section: Discussionmentioning
confidence: 99%